Cyclophosphamide-glucocorticoids versus lenalidomide-dexamethasone as treatment for multiple myeloma at first relapse after autologous stem cell transplantation – a retrospective analysis - Russell Sterrett (Elsevier, 2021)
There have been significant improvements in therapeutic options for relapsed multiple myeloma (MM) over the past two decades, with many novel agents including proteasome inhibitors, immunomodulatory agents, and more recently monoclonal antibodies demonstrating efficacy in this setting. However, there is a paucity of real-world data comparing outcomes seen in patients treated with novel agents as opposed to older agents. We report a historical single center cohort of patients diagnosed with myeloma between the years 1991–2012 in order to explore possible differences in outcomes. A total of 139 patients who underwent stem cell transplantation were included in our study. In our study, 88 patients were treated with cyclophosphamide and steroids alone at relapse whereas 51 patients were treated with Len-Dex. In the multivariate analysis, TTNT was shorter for patients who received Cyclo compared to Len-Dex (HR = 1.74; 95% CI, 1.01–2.99; p = 0.04); however, we could not detect an overall survival benefit (HR = 1.20; 95% CI 0.63–2.29; p = 0.57). Adverse event rates were similar in the two groups. In this retrospective single center analysis, Len-Dex was associated with longer TTNT compared with Cyclo at first relapse following autoSCT in MM; however its effect on overall survival in this setting was less clear.